2018
DOI: 10.1371/journal.pone.0199316
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ParAB dynamics in mycobacteria shows active movement of ParB and differential inheritance of ParA

Abstract: Correct chromosomal segregation, coordinated with cell division, is crucial for bacterial survival, but despite extensive studies, the mechanisms underlying this remain incompletely understood in mycobacteria. We report a detailed investigation of the dynamic interactions between ParA and ParB partitioning proteins in Mycobacterium smegmatis using microfluidics and time-lapse fluorescence microscopy to observe both proteins simultaneously. During growth and division, ParB presents as a focused fluorescent spot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A careful analysis of ParB positioning during the cell cycle revealed that the disruption of the ParA interaction with DivIVA altered the movement of segrosomes. It was previously shown that the ParB complex that migrates towards the new cell pole exhibits higher velocity than the one migrating towards the old cell pole (Ginda et al , ; Uhía et al ., ). Moreover, a recent visualisation of the nucleoid in relation to the localisation of ParB complexes revealed that the nucleoid is asymmetrically positioned and shifted towards the new pole and that the old pole segrosome is located close to the edge of the nucleoid throughout most of the cell cycle (Hołówka et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A careful analysis of ParB positioning during the cell cycle revealed that the disruption of the ParA interaction with DivIVA altered the movement of segrosomes. It was previously shown that the ParB complex that migrates towards the new cell pole exhibits higher velocity than the one migrating towards the old cell pole (Ginda et al , ; Uhía et al ., ). Moreover, a recent visualisation of the nucleoid in relation to the localisation of ParB complexes revealed that the nucleoid is asymmetrically positioned and shifted towards the new pole and that the old pole segrosome is located close to the edge of the nucleoid throughout most of the cell cycle (Hołówka et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the control of the mycobacterial cell cycle is crucial for pathogenicity, the orchestration of its key events remains unexplored. While previous studies have described the main components of the mycobacterial chromosome segregation machinery, the ParA and ParB proteins, and have reported ParA interaction with a polar growth determinant DivIVA homologue (named Wag31 in mycobacteria) (Jakimowicz et al, 2007;Ginda et al, 2013;Uhía et al, 2018), the exact mechanism of asymmetric chromosome segregation and the biological role of the ParA-DivIVA interaction have not been investigated. In mycobacteria, as in most studied bacterial species (Bacillus subtilis, Caulobacter crescentus, Vibrio cholerae, Myxococcus xanthus, Corynebacterium glutamicum, and Streptomyces coelicolor, but not Escherichia coli and some other γ-proteobacteria), origin of chromosomal replication (oriC) regions are organised into complexes named segrosomes by ParB binding to oriC-proximal parS sites (Chaudhuri and Dean, 2011;Wang et al, 2013;Graham et al, 2014;Zhang and Schumacher, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, the ParABS system can work as a Brownian ratchet: the ParB-bound cargo "self-drives" by both creating and following a ParA gradient over the DNA. This protein gradient-based Brownian ratchet model provides a conceptual framework that allowed us to explain -for the first time in a coherent manner -the diverse motility patterns of PCs evidenced in vivo (Hu et al 2017a) and starts to gain support from in vivo experiments (Debaugny et al 2018;Le Gall et al 2016;Schumacher et al 2017;Uhía et al 2018). However, our effort so far focused on a highly simplified picture, it is unclear 1) whether and how this Brownian ratchet mechanism can adapt the plasmid segregation distance to the length of an elongating nucleoid, and 2) how the PC partition ensures its fidelity against cellular noises.…”
Section: Introductionmentioning
confidence: 94%